Measurements and Calculations of Protein Intramolecular Vibrations in the THz Range - Niessen, K. A.; Snell, E.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
We report the calculations and measurements of intramolecular vibrational modes and their dependence on inhibitor binding in the THz range. We see an increase in anisotropic THz absorption at low frequency with inhibitor binding in both the measurements and calculations. This surprising result suggests an increase in flexibility with binding. We will discuss the possible reasons for this discrepancy.
Keywords: charmm